4x-y=32y=-2x+70 Try rearraging it. If they're all equal, then the order does not matter.2x+70=4x-y=32y-4x,-4x,+y,+y-2x+70=33y-x+35=33y
4(3x-8y = 24) 12x+32y = 96 Multiply all terms in the first equation by 4: 12x-32y = 96 12x+32y = 96 Add both equations together: 24x = 192 Divide both sides by 24 to find the value of x: x = 8 Substitute the value of x into the original equations to find the value of y: Therefore: x = 8 and y = 0
2y+8y2 can be factored to 2y(1+4y)
The sum equals the product.
The sum of a single number is itself. So the only number whose sum equals 2 is 2.
4x-y=32y=-2x+70 Try rearraging it. If they're all equal, then the order does not matter.2x+70=4x-y=32y-4x,-4x,+y,+y-2x+70=33y-x+35=33y
4(3x-8y = 24) 12x+32y = 96 Multiply all terms in the first equation by 4: 12x-32y = 96 12x+32y = 96 Add both equations together: 24x = 192 Divide both sides by 24 to find the value of x: x = 8 Substitute the value of x into the original equations to find the value of y: Therefore: x = 8 and y = 0
2y+8y2 can be factored to 2y(1+4y)
Don
The sum equals the product.
39
The expression can be factored as -12x + 32y -16z = 4(-3x + 8y - 4z) but a slightly improved presentation would be to extract -4 from the original expression. So, -12x + 32y -16z = -4(3x - 8y + 4z)
27
80x+32y=1280
the sum of 18 and a number equals 24
The sum of a single number is itself. So the only number whose sum equals 2 is 2.
6y3 + 8y2 - 15y - 20 is an expression, not an equation (or inequality). An expression cannot be solved.The expression factorises to (3y + 4)*(2y2 - 5)